The Effect of Onggok Fermentation Duration Using Probio on Physical Quality and Dry Materials - Kurniawan, Aldi; Sukaryani, Sri (Jurnal Biologi Tropis, 2025)
Feed efficiency plays a crucial role in livestock production, as feed accounts for the largest portion of total production costs. One potential way to reduce feed expenses is by utilizing agricultural by-products such as onggok (cassava residue), which is abundantly available and affordable. However, onggok has limitations in its use as animal feed due to its low protein content, high crude fiber, and the presence of anti-nutritional compounds such as cyanogenic glycosides. Fermentation is an effective method to improve the nutritional quality and physical characteristics of onggok, making it more suitable as a feed ingredient. This study aims to determine the effect of the duration of Onggok fermentation using probio on dry matter content (DM), pH value, and physical quality. This study used a completely randomized design (CRD). The treatment pattern was in accordance with the treatment, namely four treatments and each treatment was repeated three times. P0: Onggok fermentation using 0.4% probio for 0 days, P1: Onggok fermentation using 0.4% probio for 3 days, P2: Onggok fermentation using 0.4% probio for 6 days, P3: Onggok fermentation using 0.4% probio for 9 days. The variables observed were dry matter, pH value, aroma, color, and texture. The results showed that the average DM value was obtained by P0: 85.05%, P1: 82.14%, P2: 85.13%, and P3: 77.63%. The average pH value was P0: 5.3% P1: 4.6% P2: 5% P3: 3.6%. Descriptively, Onggok had a more sour aroma, the color changed to light brown, and the texture was softer than before fermentation. The study concluded that dry matter content, pH level, and changes in physical characteristics were all significantly influenced by the probio fermentation time of 0 to 9 days.